Vegetative insecticidal protein of Bacillus thuringiensis BLB459 and its efficiency against Lepidoptera. (April 2017) - Boukedi, Hanen; Ben Khedher, Saoussen; Hadhri, Rania; Jaoua, Samir; Tounsi, Slim; Abdelkefi-Mesrati, Lobna
Abstract: Bacillus thuringiensis strain BLB459 supernatant showed a promising activity against Lepidopteran pests with extremely damages in the larvae midgut. Investigations of the genes that encode secreted toxin demonstrated that this strain harbored a vip3 -type gene named vip3 (459). Based on its original nucleotide and amino acid sequences, this gene was cloned into pET-14b vector and overexpressed in Escherichia coli . The expressed protein was purified and tested against different insects and interestingly the novel toxin demonstrated a remarkable activity against the stored products pest Ephestia kuehniella and the polyphagous insects Spodoptera littoralis and Agrotis segetum . As demonstrated, the acute activity of Vip3(459) protein against A. segetum can be due to its original amino acids sequence and the putative receptors of this toxin in the larvae midgut. These results demonstrated that this Vip3 toxin showed a wide spectrum of activity against Lepidoptera and support its use as a biological control agent. Graphical abstract: Highlights: Bacillus thuringiensis strain BLB459 supernatant is active against Lepidoptera. B. thuringiensis strain BLB459 harbored a vip3 -type gene named vip3 (459). Vip3(459) toxin demonstrated a remarkable activity against lepidopteran pests. The acute activity of Vip3(459) against A. segetum can be due to its sequence. This activity can be also due to the putative receptors of this toxin in the midgut.